Spectral and mineralogical effects of heating on CM chondrite and related asteroids - Sidhu, S.; Cloutis, E.A.; Mann, P.; Applin, D.; Hiroi, T.; Mengel, K.; Kareta, T.; Reddy, V.; Beck, P.; Mertzman, S.A. (Icarus (New York, N.Y. 1962), 2023)
Several carbonaceous chondrites (CCs) display evidence of aqueous and thermal alteration. However, the process of thermal alteration is not fully understood. To investigate the spectral variations caused by thermal alteration, we heated powders of CM2 CCs Murchison and Jbilet Winselwan, as well as a simulant Murchison mixture (WMM) and its end members. Heating was conducted up to 1200 °C, in 100 °C increments under a purified nitrogen environment. We also compared the findings of our study with results of previous heating experiments conducted on CCs to better understand the effect differing conditions have on the spectral properties observed. Formation of Fe3+ oxyhydroxides and the decomposition of serpentine due to heating are confirmed by both reflectance and X-ray diffraction (XRD) data. Fe3+ oxyhydroxides features such as a steep slope in between 350 to ∼700 nm, and an ∼850 nm feature can be seen starting at ∼300 and 400 °C, respectively. The serpentine-associated features start to decompose at ∼700 °C and disappear by ∼900 °C. Spectra >1000 °C are generally dark and featureless and above this temperature, mafic silicate absorption bands begin to appear. Our results show that heating-induced spectral variations are evident, and the nature of these changes depends on various parameters including temperature, experimental conditions, duration of heating, sample grain size, as well as mineralogical changes accompanying heating, and heterogeneity between CCs. •CM2 Murchison and Jbilet Winselwan and analogues were subject to heating experiments to temperatures up to 1200 °C.•Several spectral metrics were identified to characterize the spectral properties of the samples.•Temperature and environmental conditions are the most dominant factors controlling the observed spectral variations.•Other factors include differences in grain size, mineralogy, and the duration of heating.•Spectral variations are also caused by the heterogeneity between carbonaceous chondrites.